Soupe ou Harira: deux modèles politiques de l’interculturel culinaire - Bernoussi, Mohamed (E|C, 2020)
What I call the culinary intercultural can be understood in two ways: either the study of travelers' reactions to culinary phenomena, or the comparative study of dishes in two or more different cultures, which will be the subject of the main part of this contribution.